Networks of High Aspect Ratio Particles to Direct Colloidal Assembly Dynamics and Cellular Interactions. (15th September 2020) - Finbloom, Joel A.; Demaree, Benjamin; Abate, Adam R.; Desai, Tejal A.
Abstract: Injectable colloids that self‐assemble into 3D networks are promising materials for applications in regenerative engineering, as they create open systems for cellular infiltration, interaction, and activation. However, most injectable colloids have spherical morphologies, which lack the high material‐biology contact areas afforded by higher aspect ratio materials. To address this need, injectable high aspect ratio particles (HARPs) are developed that form 3D networks to enhance scaffold assembly dynamics and cellular interactions. HARPs are functionalized for tunable surface charge through layer‐by‐layer electrostatic assembly. Positively charged chitosan‐HARPs have improved particle suspension dynamics when compared to spherical particles or negatively charged HARPs. Chit‐HARPs are used to improve the suspension dynamics and viability of MIN6 cells in 3D networks. When combined with negatively charged gelatin microsphere (GelMS) porogens, chit‐HARPs reduce GelMS sedimentation and increase overall network suspension, due to a combination of HARP network formation and electrostatic interactions. Lastly, HARPs are functionalized with fibroblast growth factor 2 (FGF2) to highlight their use for growth factor delivery. FGF2‐HARPs increase fibroblast proliferation through a combination of 3D scaffold assembly and growth factor delivery. Taken together, these studies demonstrate the development and diverse uses of high aspect ratio particles as tunable injectable scaffolds for applications in regenerative engineering. Abstract : High aspect ratio particles (HARPs) are fabricated from polycaprolactone and functionalized via layer‐by‐layer assembly with chitosan and heparin to develop injectable colloidal scaffolds. HARPs form entangled networks with improved suspension dynamics compared to spherical particles. HARPs can be used to improve cellular dynamics and viability, facilitate mixed particle co‐assemblies, and initiate growth factor delivery for regenerative engineering applications.